COVID-19, Dissensus and de facto Transformation at the South Africa–Zimbabwe Border at Beitbridge. Issue 4 (8th August 2022) - Moyo, Inocent
ABSTRACT: This paper explores the coronavirus-induced closure of the South Africa–Zimbabwe border at Beitbridge and its effects on informal cross-border trade activities and migration. It is based on a qualitative study involving in-depth interviews with informal cross-border traders (ICBTs), migrant workers, local informal transporters, informal cross-border transporters, bus drivers, and individual couriers (hired to transport goods across illegal border cross border points). The findings suggest that the border closure had a limited impact on ICBT and migration behavior as it led to a transformation and/or reconfiguration of how people contested the Beitbridge border. This suggests that border closures are an ineffective strategy to mitigate the effects of disasters/pandemics, such as coronavirus.